Microbottle resonator for formaldehyde liquid sensing - Johari, Md Ashadi Md; Al Noman, Abdullah; Abdul Khudus, Muhammad Imran Mustafa; Jali, Mohd Hafiz; Yusof, Haziezol Helmi Mohd; Harun, Sulaiman Wadi; Yasin, Moh (Elsevier, 2018)
We have successfully investigated the use of a whispering gallery mode (WGM) optical micro-bottle resonator (MBR) for liquid formaldehyde (CH 2 O) sensing. The MBR was fabricated via the “soften-and-compress” method to create a bulge (bottle) structure with a bottle diameter of 190 μm. The MBR was optically excited by using a non-adiabatic 2 μm optical microfiber and was found to have a Q-factor of >10 5 . The MBR was then employed to measure formaldehyde concentration within 1–5% range and the performance was compared with a bare microfiber. The MBR sensor was found to have a sensitivity of 4.397 dB/% with 90% linearity which were superior to the bare microfiber. The MBR sensor was also found to have good repeatability and stability over a period of 60 min. This indicates that MBR sensor has a great potential to be employed as a low cost formaldehyde liquid sensor.